EVALUATION OF USING AMNIOTIC MEMBRANE DRESSING IN SUPERFICIAL BURNS - Qader, Ari Raheem; Rasul, Faraydoon Karim (Journal of Sulaimani Medical College, 2011)
Background The use of amniotic membrane as a biological dressing for thermal injury is simple and cheap and has been found to be superior to allograft and xenograft. The membrane prevents heat and water loss from the wound surface and acts as a barrier against bacterial contamination, thus aiding the healing process and reducing morbidity. Another clinically significant and important property of the membrane is its ability to offer marked relief from pain. Objective The main aim of this study was to treat superficial burn by amniotic membrane and test the effectiveness of amniotic membrane as an enhancer of wound healing. Patients and Methods Between 1/6/2007 to 1/6/2009, (200) patients with partial thickness burn were treated by amniotic membrane at Sulaimani burn and reconstructive surgery hospital). The burn wound was covered with amniotic membranes procured from hepatitis, syphilis and HIV-seronegative mothers having undergone cesarean deliveries. The wounds were inspected for any signs of infection weekly for 4 weeks, then monthly for 2-3 months thereafter. Results The Amniotic membrane mostly applied in the same day of burn 129 (64.5 %), in 42 cases (21%) they were applied in the second day of burn. The rest of the patient had the amniotic membrane applied in the day three and more. When the outcome was compared by characteristics of the patient there was no significant difference by sex, cause of burn, site of burn, but there is a significant difference in outcome by age group. Conclusion Amniotic membrane dressing in superficial wound was effective, the application of this cheep dressing material warrants further study, as it can be useful in areas where dressing are expensive and specialized equipment is not available.
Keywords: Amniotic membrane; Superficial burn; Burn dressing